Residue Kinetics of Ethofumesate in Texturally Diverse Soils of Sugar Beet Crop under Field Conditions - Shishir Tandon; Suman Lata Pal (Journal of Chemistry)
Indiscriminate use of pesticides and growing awareness of environmental and health problems had led to monitoring their residues in soil and crops. Ethofumesate is one of the widely used herbicides for controlling weeds in sugar beet. Dissipation kinetics and terminal residues of ethofumesate were investigated in two diverse soils under subtropical field conditions. Ethofumesate dissipated slowly after application and follows biphasic first-order kinetics in soils. The average half-life for initial and later phases in sandy loam soil, respectively, was 14.54 and 20.42 and 51.83 and 65.21 days, while for silty clay loam, it was 10.09 and 13.00 and 71.42 and 73.10 days, respectively. Recoveries in soil, leaves, and beetroot ranged from 78.15 to 88.05, 77.01 to 88.58, and 76.25 to 84.50%, respectively. The quantitation limit for soil, roots, and leaves was 0.002 μg g−1. At harvest, no residues were detected in soils, leaves, and sugar beetroots. Residues were below the maximum residue limits in sugar beetroots and leaves as set by EU (0.2 ppm). Ethofumesate is safe from weed control and environmental aspects as it does not persist for a long duration in soils and does not appear to pose any adverse effect on human/animal health under subtropical field conditions.